Penyuluhan dan Pengenalan Penyakit Rabies di Kelurahan Bugis Kec. Sumbawa Kab. Sumbawa - Abdul Hamid; Putri Adekayanti; Lina Eta Safitri; Hamdin Hamdin (Pusat Riset dan Inovasi Nasional, 2023)
. Rabies, also called mad dog disease, is an acute infectious disease of the central nervous system caused by the rabies virus. Every year more than 55,000 people die from rabies and more than 15 million people throughout the world receive prophylactic anti-rabies vaccine treatment. How rabies is transmitted through bites and non-bites (scratches or licks on open skin/mucosa) by animals infected with the rabies virus. This activity aims to increase public knowledge regarding the spread of rabies. This community service activity method consists of several stages, including dialogue and coordination with partners, preparation facilities and infrastructure, implementation of activities and evaluation. The activity was carried out in the form of education regarding rabies and its spread. This activity was attended by 32 participants in the Bugis sub-district RT 03/ RW 04. The participation and activeness of the residents in taking part in this activity was very good, as evidenced by the participants being able to answer almost all the questions in the posttest. Re-exposure was given to participants who were unable to answer or answered incorrectly on the posttest. It is hoped that this activity can become a routine and sustainable rabies prevention effort to eradicate rabies in the district. Sumbawa.